Reniscymnus gen. nov., a new genus of Scymnini (Coleoptera, Coccinellidae) from the Oriental region - Feng Peng; Mingjie Tang; Xingmin Wang; Xiaosheng Chen (ZooKeys)
Ladybird beetles (Coleoptera, Coccinellidae) are a species-rich, ecologically diverse and economically important group of insects. A new ladybird genus of Scymnini, Reniscymnus gen. nov., is described from China and Laos, along with two new species, Reniscymnus cordatus Peng & Chen, sp. nov. and Reniscymnus explanatus Peng & Chen, sp. nov. This newly identified genus can be distinguished from the remaining members of the tribe Scymnini by its short antenna consisting of eight antennomeres and an inflated antennal club bearing two extremely long setae; the narrow frons; the slightly tapering apically terminal maxillary palpomere; as well as the recurved and laterally almost complete abdominal postcoxal lines that enclose a distinctly wide area. Detailed morphological descriptions, illustrations, and a key to identify these two species within the new genus are provided. Morphological similarities and relationships of the new genus with other genera of Scymnini are discussed.